Floristic studies of Pulau Jarak And Pulau Perak, Malaysia - Wati Haron, Noorma (Malaysian Journal of Science, 2017)
Preliminary studies on the flora of Pulau Jarak and Pulau Perak have been carried out. Some of the common species at Pulau Jarak were Barringtonia asiatica, Dracaena maingayi, Eugenia grandis, Ficus sp. and Scaevola frutescens. Several herbs were very common such as Aglaonema schottianum, Labisia pumila and Phylllanthus frondosus. The common climbers observed were Aristolochia ungulifera, Gnetum sp., Hoya parasitica and Smilax helferi. Ferns such as Angiopteris evecta, Asplenium nidus, Dicranopteris linearis, Pyrrosia sp. and Stenochlaena palustris were also common. The common palms were Caryota mitis and Oncosperma filamentosa. Ficus sp., Lygodium sp. and Stenochlaena palustris were among the common species observed at Pulau Perak. Barringtonia asiatica, Eugenia grandis and Scaevola frutescens were the typical species of the coastal forest vegetation while Caryota mitis, Dracaena maingayi, Ficus sp. and others formed the inland forest vegetation. In terms of floral diversity, Pulau Perak vegetation showed less diversity compared to Pulau Jarak.